Implementation of csr on company value in the real estate sector - Wijaya, Suryanto; Munandar, Agus (Enrichment : Journal of Management, 2024)
This research aims to investigate the implementation of Corporate Social Responsibility (CSR) as a form of social responsibility of real estate companies to the surrounding community. The method used in this study was a literature review sourced from several previous studies. The research results indicate that the form of CSR implementation is considered an indicator that is able to influence the company's value in the perception of the surrounding community. However, in previous research, there is also a contradiction in that CSR is considered unable to have a significant influence on company value. Real estate companies are considered to have a substantial impact on the economic, social, and environmental aspects of society. Real estate companies carry out corporate social responsibility to reduce negative impacts and increase positive contributions to society by participating in sustainability projects, such as supporting the construction of transportation routes and so